Answer:
x = 3 is a true solution.
The zeros of 0 = x2 – 5x + 6 are possible solutions to the radical equation.
Explanation:
Given in the question an equation,
√(x-2) - 4 = x - 6
√(x-2) = x - 6 + 4
√(x-2) = x -2
Take square on both sides of the equation
√(x-2)² = (x -2)²
x - 2 = x² - 4x + 4
0 = x² - 4x - x + 4 + 2
0 = x² - 5x + 6
a = 1
b = -5
c = 6
x = -b±√(b²-4ac) / 2a
x = -(-5)±√(5²-4(1)(6)) / 2(1)
x = 5 ± √1 / 2
x = 5 + 1 / 2 or 5 - 1 /2
x = 3 or x = 2
Plug value of x in the radical equation:
x=3
√(3-2)-4=3-6
√1 -4 = -3
1 - 4 = -3
-3 = -3
x=2
√(2-2)-4=2-6
0 - 4 = -4
-4 = -4